BIOGARDEN BERBASIS RUMPUT VETIVER UNTUK PENGOLAHAN AIR LIMBAH PROSES PENGOLAHAN KOPI: SOLUSI INOVATIF UNTUK LINGKUNGAN BERKELANJUTAN DI SAWANGAN, MAGELENG - Mardhatilah, Dina; Afroda, Helmi; Faizah, Kuni; Firmansyah, Eric (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The empowerment of farmers in Ketep Village, Sawangan, Magelang is an important step to increase their independence, creativity, and productivity. In addition to being involved in coffee processing, farmers in this area are also active in vegetable cultivation. However, the coffee processing process produces liquid waste with a very acidic pH if it is directly discharged into water bodies or soil, which can damage the environment and negatively impact the quality of the plants grown and endanger consumer health. Coffee liquid waste contains high organic matter, which can increase Biochemical Oxygen Demand (BOD) and Chemical Oxygen Demand (COD) in waters if disposed of carelessly. To overcome this problem, we propose a community service program that utilizes vetiver-based biogardens as a method of liquid waste management. As a PKM partner in this service is the "Beringin Farmers Group" in Ketep Village, Sawangan District, Magelang. The results of the survey on the understanding of the use of vetiver grass as an absorption of coffee processing liquid waste show that a small percentage of respondents do not fully understand or are interested in this topic. Most of the respondents were in the category of high understanding or interest (score 4-5), which indicates a significant impact of counseling. The results of the observations showed that the filtration of coffee liquid waste using vetiver grass succeeded in significantly lowering the pH, BOD, and COD. This filtration process increases the pH of the waste from 4 (acidic pH) to 7 (neutral pH). The content of BOD and COD decreased significantly from week 0 to week 3, which suggests that vetiver root is effective in reducing the content of organic matter and harmful chemical compounds in coffee liquid waste.